The Academic Journal: Has it a Future? - Weiner, Gaby (Education Policy Analysis Archives, 2001)
This article examines the current state of the academic journal. It does so for a number of reasons: the increasing expense of paper journals; the advent of electronic publishing; the use of publication in journals as an indicator of research quality (in addition to disseminating knowledge within a discipline) and consequent criticisms of systems of peer review and evaluation of scholarship; emergent issues of equity and access; and evidence of malpractice. These issues taken together constitute a critique of, and challenge to, the process whereby research papers become journal articles, which has in the past been viewed as unproblematic and straightforward. This paper brings together a wide range of literature in order to inform discussion about the future of the academic journal. It briefly examines the origins of the academic journal and then provides a comprehensive overview of current debates concerning how academic journals work today. In so doing, it raises questions about decisions that will need to be taken regarding the continuity or otherwise of the conventional academic journal, and how publishing practices may change in the future.